A macroeconomic determinants of housing price in Malaysia / Muhammad Khairul Izhar Rabi’i - Rabi’i, Muhammad Khairul Izhar (Faculty of Business and Management, 2018)
The purpose of this study is to determine the significant relationship of macroeconomics toward house price in Malaysia from 3rd Quarter 2006 to 2nd Quarter 2017. The variables that being use in this study is Gross Domestic Product (GDP), Interest Rate (INT) and Money Supply (MS) as independent variables while Malaysia Housing Price Index (MHPI) as dependent variable. This paper applies Ordinary Least Square (OLS) methods in order to define the relationship among the variables. In short run, the results shows gross domestic product have a positive significant relationship and interest rate have a negative significant relationship Malaysia housing price. However, money supply found no significant relationship toward Malaysia housing price.